Pengaruh Komitmen Organisasi, Sistem Pengendalian Internal, Moralitas Individu, Dan Itegritas Terhadap Kecenderungan Kecurangan (Fraud) Pada Pengelolaan Keuangan Desa (Studi Empiris Pada Desa Se-Kabupaten Buleleng) - Anggara, Made Rio; Sulindawati, Ni Luh Gede Erni (Universitas Pendidikan Ganesha, 2020)
The research aims to determine the influence of organizational commitments, internal control systems, individual morality, and the integrity of fraud on the financial management of villages in Buleleng Regency. This type of research is quantitative research. The population used is all village apparatus in Buleleng Regency. The sampling techniques in this study used purposive sampling methods. By using samples of 186 village apparatus. Data is obtained from the dissemination of questionnaires directly to respondents. Data analysis in this study uses descriptive analysis, data quality tests, classical assumption tests, multiple linear regression analyses and hypotheses testing with the help of SPSS version 23.0 program.Â The results showed that 1) the organizational commitments negatively and significantly affect the fraud tendencies, 2) internal control systems negatively and significantly affect the tendencies of fraud; 3) Individual morality affects negatively and significantly against the tendencies of fraud; and (4) the integrity negatively and significantly affect the fraud tendencies.